(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The main purpose of this study was to examine the relationship between work satisfaction and happiness among teachers in the International Baccalaureate Diploma Programme (IBDP). This study employed a quantitative approach following multiple regression analysis. Adapted research instruments in the form of questionnaires were utilized and generated each variable’s Cronbach’s alpha (α) for internal consistency. Multicollinearity issues were also addressed through their tolerance and VIF values. The questionnaires were used to collect IBDP teachers’ numerical data using Likert scales and were analyzed using SPSS. Results revealed that four significant elements emerged in order to fulfill teachers’ happiness. Propositions were crafted based on the results of the study that led to the development of a theory called Synergistic Well-Being of Teachers Theory which suggested that the nexus between work satisfaction and happiness among the IBDP teachers was shaped by four elements: self-esteem, stress factors, work environment, and security of tenure.